INCIDENCE OF POST INFLAMMATORY HYPERPIGMENTATION, HIRSUTISM, AND PHOTOSENSITIVITY WITH THE USE OF WHITENING CREAMS AVAILABLE OVER THE COUNTER IN THE LOCAL POPULATION - RAFIQUE , S; ULLAH , MA; IQBAL , R (Biological and Clinical Sciences Research Journal, 2023)
This cross-sectional study investigated the incidence of post-inflammatory hyperpigmentation, hirsutism, and photosensitivity associated with using over-the-counter whitening creams in the local population. A total of 699 participants from the Gulab devi teaching hospital Lahore from 1 January 2022 to 31 December 2022 were included in the study. Data was collected through face-to-face structured questionnaires, capturing demographic information, whitening cream usage patterns, and reported side effects. Descriptive statistics were employed to analyze the data. The results revealed that most participants were female (59.23%) and fell within the age group of 26-35 years (35.77%). Type III (Light to Medium) skin was the most common, with 210 participants (30.06%). Type IV (Medium to Olive) skin followed closely, with 240 participants (34.31%). Type V (Dark Brown) skin was represented by 128 participants (18.34%)Regarding whitening cream usage, the most common frequency reported was once daily (45.64%), and a significant proportion of participants had been using the cream for less than 6 months (31.04%). The reported incidence of side effects demonstrated that post-inflammatory hyperpigmentation was the most prevalent (12.45%), followed by hirsutism (7.01%) and photosensitivity (4.43%). The study highlights the importance of public awareness regarding the potential risks of using over-the-counter whitening creams. It emphasizes the need for tailored recommendations based on individual skin types and the promotion of safer alternatives for achieving desired skin appearance and health. In conclusion, this study provides valuable insights into the demographic characteristics, whitening cream usage patterns, and reported side effects among individuals using over-the-counter whitening creams in the local population. It is a foundation for raising awareness, promoting informed decision-making, and encouraging safer skincare practices to enhance skin health and well-being.